Physical meaning of the QTAIM topological parameters in hydrogen bonding - Duarte, Darío Jorge Roberto (2014)
This work examined the local topological parameters of charge density at the hydrogen bond (H-bond) critical points of a set of substituted formamide cyclic dimers and enolic tautomers. The analysis was performed not only on the total electron density of the hydrogen bonded complexes but also on the intermediate electron density differences derived from the Morokuma energy decomposition scheme. Through the connection between these intermediate electron density differences and the corresponding differences in topological parameters, the meaning of topological parameters variation due to hydrogen bonding (H-bonding) becomes evident. Thus, for example, we show in a plausible way that the potential energy density differences at the H-bond critical point properly describe the electrostatics of H-bonding, and local kinetic energy density differences account for the localization/delocalization degree of the electrons at that point. The results also support the idea that the total electronic energy density differences at the H-bond critical point describe the strength of the interaction rather than its covalent character as is commonly considered.